EFISIENSI PRODUKSI USAHA TANI TEMBAKAU DI INDONESIA - Wahdini Wahdini; Murtala Murtala; Ichsan Ichsan; Hijri Juliansyah (Jurnal Ekonomi Pertanian Unimal, 2023)
This study examined the efficiency of tobacco farming production in Indonesia. This study used secondary data in the form of Data Envelopment Analysis (DEA) using the Costan Return to Scale (CRS) and Return to Scale (VRS) approaches from 2006 to 2020 from the Central Bureau of Statistics and FAO. Development analysis Data (DEA) method was used to analyze the efficiency of tobacco farming production in Indonesia. The results indicated that the 4 input variables consisting of land area, investment, production costs, and output Tobacco production were in the CRS and VRS approaches. For CRS, there were 6 efficient years, while for VRS, there were 7 efficient years. The average value of efficiency in tobacco farming is one (1,000).